Evaluasi Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Kas Sebagai Alat Pengendalian Internal - Bintang Kusucahyo; Yohana Merina (Akubis : Jurnal Akuntansi dan Bisnis, 2022)
This study aims to evaluate the cash receipts and disbursement accounting information system as a means of internal control in the study of the Kasih Sejahtera Abadi Cooperative, Kedungrejo Village, Rowokangkung District, Lumajang Regency. The type of research used is a case study. Sources of data used are primary data and secondary data, data collection techniques used are observation, interviews, and documentation. The problem with cooperatives is that there is a dual function of the administrator treasurer with the finance section and the accounting section and also the chairman with the cooperative manager, the documents used by the cooperative are incomplete, the accounting records used by the cooperative are incomplete, and the application of the cash receipts and disbursement accounting information system is still incomplete. manuals. Evaluation results by separating the functions of the management treasurer, finance section, accounting section, chairman and cooperative manager, adding the documents used in the form of proof of member deposit transactions, repayment of member loans, and member loans. In addition to adding accounting records used in the form of member loan recapitulation, member loan repayment, cash receipts journal and daily cash journal, and improving cash receipts and disbursement accounting information system procedures so that the cooperative's internal control system will be effective and efficient.